Folate Metabolism and Its Implications in Pregnancy - Puspitasari, Maya Khaerunnisa; Irianti, Setyorini; Pramatirta, Akhmad Yogi; Wirawan, Wahyudi; Islamy, Nurul; Maelissa, Merlin Margreth; Lumentut, Anastasia Mariane (Newinera Publisher, 2025)
The impact of folate nutritional status on a variety of pregnancy outcomes has been acknowledged for a considerable period of time. Folate is increasingly recognized not just as a nutrient required to prevent megaloblastic anemia during pregnancy, but also as a vitamin necessary for reproductive health. Folate plays an important role in several metabolic processes including DNA synthesis and methylation. Changes in folate status can affect the stability and integrity of DNA or affect the methylation patterns of some tissues. Folate is required for cell division and cell maintenance, as it acts as a co-enzyme in the transfer and processing of carbon units and plays an important role in the synthesis of nucleotides (thymidine) that are essential for de novo construction or DNA repair. The purpose of this article is to examine the function of folic acid in human health especially in pregnancy and to evaluate the benefits, concerns, and epigenetic effects of maternal FA in light of recent discoveries that are crucial for the development of future research.